Analisis Penggunaan Bahasa Gaul di Media Sosial: Instagram - Nainggolan, Elizabet; Putri Farida Sitorus, Agnes; Clarisa Sianipar, Lusya; Ihsan Abdul Rahsyid, Rahwul; Horas Ferdinand Manurung, Alphin; Rosmaini, (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This research examines the use of slang on the social media Instagram among teenagers and its impact on the development of the Indonesian language. Using qualitative research methods, data was collected through non-participant observation of Instagram content such as stories, comments and captions, as well as questionnaires distributed to 10 respondents. The research results show that the main motivation for using slang on Instagram is to facilitate communication (60%) and keep up with current developments (80%). The forms of slang found include abbreviations, puns on words, and language mixing. Factors that influence the use of slang include current developments, the role of the media, expressions of togetherness, and group identity. This research also identifies the positive and negative impacts of using slang, including potential threats to the existence of standard Indonesian. In conclusion, although slang makes communication easier and is considered interesting, its use needs to be adapted to the situation and context to preserve the Indonesian language.